THE EFFECTIVENESS OF NONPHARMACOLOGICAL INTERVENTIONS IN REDUCING DISCOMFORT DURING PREGNANCY - Dewi Susanti (International Journal of Multidisciplinary Research and Literature, 2025)
Pregnancy is a physiological process accompanied by various anatomical, hormonal, biomechanical, and psychological changes that often cause discomfort such as nausea, vomiting, low back pain, leg cramps, fatigue, constipation, sleep disturbances, edema, and anxiety that can affect the quality of life of pregnant women. This study aims to analyze the effectiveness of various nonpharmacological interventions in reducing discomfort during pregnancy through a systematic literature review approach. This study uses the PRISMA 2020 guidelines in the process of identifying, selecting, and synthesizing scientific articles obtained from Google Scholar with a publication range of 2021–2026. The articles analyzed included experimental, quasi-experimental, randomized controlled trials, systematic reviews, and meta-analyses that discussed interventions such as antenatal yoga, acupressure, massage, deep breathing relaxation, aromatherapy, and mindfulness in pregnant women. The results of the synthesis showed that nonpharmacological interventions consistently had a positive impact in reducing physical and psychological complaints during pregnancy, including a decrease in pain intensity, nausea and vomiting, anxiety, as well as improved sleep quality and comfort of pregnant women. The working mechanism of this intervention is related to the regulation of the autonomic nervous system, increased relaxation, and modulation of physiological stress responses. In conclusion, nonpharmacological interventions are a complementary approach that is effective, safe, and potentially integrated in evidence-based obstetric care to improve maternal well-being during pregnancy.